Pembentukan Karakter Disiplin bagi Siswa - Ahmad Taufik; Muhamad Akip (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2021)
This paper presents the role of Moslem education in shaping the character of student discipline. Many public school students still underestimate morality, manners, and disciplined behavior. Therefore, education is the center of Islam and the best solution to shape student discipline. Islamic education may be a method of deepening and appreciating knowledge. In this process, students learn Islamic values through the expansion and development of their natural abilities. They notice their potential for equality and excellence in life. The analysis methodology employed in this research is descriptive analysis; a collection of data and sources to analyze, explain critically, and understand more systematically the role of Islamic education in shaping student discipline. The results of the research show that the benefits of Islamic education can shape student discipline, including providing religious material, guidance, advice, recommendations, and role models for educators.